A case of chronic granulomatous craniofacial osteomyelitis. (2018) - Sharma, Vidhu; Kaushal, Darwin; Elhence, Poonam
Abstract: We present the clinical image of a 56-year old male who presented with chronic multiple craniofacial discharging sinuses with lytic, sclerotic destruction of facial bones on radiology causing gross facial deformity. He remained undiagnosed for years. The diagnosis was clinched on histopathology as a chronic granulomatous osteomyelitis showing Actinomyces.